Epigenetics: Beyond Chromatin Modifications and Complex Genetic Regulation. Issue 3 (28th May 2014) - Eichten, Steven R.; Schmitz, Robert J.; Springer, Nathan M.
Abstract : Epigenetics and chromatin modification engage complex gene regulatory systems in plants . Abstract: Chromatin modifications and epigenetics may play important roles in many plant processes, including developmental regulation, responses to environmental stimuli, and local adaptation. Chromatin modifications describe biochemical changes to chromatin state, such as alterations in the specific type or placement of histones, modifications of DNA or histones, or changes in the specific proteins or RNAs that associate with a genomic region. The term epigenetic is often used to describe a variety of unexpected patterns of gene regulation or inheritance. Here, we specifically define epigenetics to include the key aspects of heritability (stable transmission of gene expression states through mitotic or meiotic cell divisions) and independence from DNA sequence changes. We argue against generically equating chromatin and epigenetics; although many examples of epigenetics involve chromatin changes, those chromatin changes are not always heritable or may be influenced by genetic changes. Careful use of the terms chromatin modifications and epigenetics can help separate the biochemical mechanisms of regulation from the inheritance patterns of altered chromatin states. Here, we also highlight examples in which chromatin modifications and epigenetics affect important plant processes.